A Step to Improve Pharmacovigilance System: A Cross Sectional Study among Outpatients Visiting Multi Super Speciality Hospital in Kerala Established with ADR Monitoring Centre - Basheera, Veerankutty; Shahnas, Thahmina; Thankappan, Sneha; Salam, Sumayya (Journal of Pharmacy Practice and Community Medicine)
Objectives: To evaluate knowledge and awareness about ADR and Pharmacovigilance system among out patients visiting different department of a super speciality hospital. Secondary objective is to sensitize patients on ADR reporting system. Materials and Methods: A cross sectional study was conducted at multi super speciality hospital. The Outpatient visiting various departments of the hospital (KIMS Alshifa multi-specialty hospital Perinthalmanna) for medical care were randomly selected and demographic details of respondents were noted. Questionnaire regarding knowledge and perception towards ADR developed for the study. The questionnaire and demographic data form given in two languages (Malayalam and English). A patient information leaflets were prepared and distributed among the study participants. Patients were trained on usage of ADR PvPI app for self reporting ADR. The data analyzed by descriptive analysis. Results: This study investigated and assessed the knowledge and perceptions of ADR among out patients visiting tertiary care hospital. The study comprised of 50 patients. Most of the participants were not aware about Pharmacovigilance (56%), the important source on awareness on Pharmacovigilance was social media and internet. Around 15(30%) respondents have experienced ADR after taking medication, but only 10 patients reported it to their physician. Most of them don’t consider ADR reporting as necessary. Difficulty in travelling and rush in the hospital were the other reasons for under reporting ADR. All the participants were not aware about the Pharmacovigilance centre at the institution. Most of them prefer to report ADR directly to their physician. About 96% of patients were not heard about the ADR PvPI app. Conclusion: All the participants were trained on how to use the ADR PvPI app for self reporting ADR. A patient information leaflet were distributed to all the participants to create an awareness about ADR and the leaflet included information on Pharmacovigilance centre of the institution and how to report ADR once occur.
Keywords: Pharmacovigilance; Adverse drug reactions; Drug safety; ADR PvPI